2014
DOI: 10.2147/ott.s55344
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of Neu1 sialidase with oseltamivir phosphate (Tamiflu®) disables cancer cell survival in human pancreatic cancer with acquired chemoresistance

Abstract: Background:Resistance to drug therapy, along with high rates of metastasis, contributes to the low survival rate in patients diagnosed with pancreatic cancer. An alternate treatment for human pancreatic cancer involving targeting of Neu1 sialidase with oseltamivir phosphate (Tamiflu ® ) was investigated in human pancreatic cancer (PANC1) cells with acquired resistance to cisplatin and gemcitabine. Its efficacy in overcoming the intrinsic resistance of the cell to chemotherapeutics and metastasis was evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 68 publications
(141 reference statements)
5
67
0
Order By: Relevance
“…It follows that the therapeutic efficacy of oseltamivir phosphate targeting Neu1 may disrupt these molecular signaling pathways. Given the ability of oseltamivir phosphate to increase E-cadherin expression and decrease N-cadherin and VE-cadherin expression as previously reported by us [46], tumors treated with this drug may become more adherent to the surrounding tissue and not metastasize as our data indicated. We propose here a graphical abstract (Figure 2) illustrating that the Snail-MMP9 signaling axis maintains several important cancer growth factor receptor signaling platforms in promoting Neu1-MMP9 crosstalk in complex with glycosylated receptors.…”
Section: A Novel Egfr-signaling Platform and Its Targeted Translationsupporting
confidence: 79%
See 2 more Smart Citations
“…It follows that the therapeutic efficacy of oseltamivir phosphate targeting Neu1 may disrupt these molecular signaling pathways. Given the ability of oseltamivir phosphate to increase E-cadherin expression and decrease N-cadherin and VE-cadherin expression as previously reported by us [46], tumors treated with this drug may become more adherent to the surrounding tissue and not metastasize as our data indicated. We propose here a graphical abstract (Figure 2) illustrating that the Snail-MMP9 signaling axis maintains several important cancer growth factor receptor signaling platforms in promoting Neu1-MMP9 crosstalk in complex with glycosylated receptors.…”
Section: A Novel Egfr-signaling Platform and Its Targeted Translationsupporting
confidence: 79%
“…Indeed, the desialylation activity of Neu1 has been shown to regulate cancer growth, and its selective inhibition has demonstrated significant therapeutic results in murine models of cancer. Neu1 inhibition by oseltamivir phosphate has been shown to specifically increase E-cadherin expression and to decrease N-cadherin expression in pancreatic cancer [30, 46], triple-negative breast cancer [112] and in ovarian tumor models [206]. This shift in E- and N-cadherin expression may obstruct the occurrence of EMT in drug-resistant phenotypes, prevent cancer cell metastases, and improve the drug sensitivity of chemoresistant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that this process is initiated by the desialylation of receptor tyrosine kinase. It has been reported that OP has anti-cancer activity against pancreatic, ovarian, and triple-negative breast cancer cell types 48,75. OP has been shown to inhibit the Neu1 sialidase activity of LPS-stimulated BMC2 macrophage cells60 and EGF-stimulated PANC1 cells 59.…”
Section: Discussionmentioning
confidence: 99%
“…Neu hydrolyzes terminal N- or 0-acylneuraminic acids which are α2,6-, α2,3-, or α2,8-linked (rate: α2,6>α2,3>α2,8) to glycoconjugates. Oseltamivir phosphate (OP) solution was prepared by dissolving 75 mg Tamiflu (Hoffman-La Roche Ltd., Basel, Switzerland) capsule in sterile 1× phosphate-buffered saline (PBS) followed by centrifugation at 1,000 rpm for 10 minutes 48. The stock extracted OP at 20 mg/mL was characterized to have identical properties as the pure OP compound 48.…”
Section: Methodsmentioning
confidence: 99%